Designing Instructional Media for Deaf and Blind Students : Promoting Inclusivity and Equity - Hendrik Siswono; Arie Eko Cahyono; Inna Hamida Zusfindhana (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to design specialized instructional media for college students with hearing and visual impairments, supporting their unique learning needs. This study used a qualitative single-case study approach to thoroughly investigate the experiences of deaf and blind college students, with a focus on instructional modules and videos. The research subject is college students with hearing and visual impairments, specifically examining their higher education experiences and identifying specific requirements for effective learning. This research instrument uses surveys, interviews, and analysis of instructional modules and videos to gather comprehensive data on the challenges and needs of deaf and blind college students. The data were analyzed using thematic analysis to identify patterns, themes, and insights related to the higher education experiences of students with hearing and visual impairments. The results of this study indicate that the design and implementation of specialized instructional media with tailored features significantly contribute to addressing the unique challenges faced by deaf and blind college students. This approach fosters inclusivity and equity, providing valuable insights for creating more effective and accessible online learning materials in higher education.